Diagnosis of depression and other patient factors impacts length of stay after total knee arthroplasty - Cheongeun Oh, PhD; Heather Gold, PhD; James Slover, MD, MS (Arthroplasty Today, 2020)
Background: The length of in-hospital stay (LOS) is an important measure of efficiency in the use of hospital resources and care quality outcomes after orthopaedic surgery. This study investigated the influence of patients' characteristics including demographic factors and the presence of comorbid preoperative depression on LOS after primary total knee arthroplasty (TKA). Methods: Data were extracted from the California Healthcare Cost and Utilization Project database for hospital discharges after primary TKA for adults aged 50 years and older from 2007 to 2010 (n = 133,603). LOS was defined as the difference in days between the date of admission and the date of discharge. We included demographic data (age, sex, race), comorbidity of depression, and years of admission as covariates in the multivariable model. Negative binomial regression was used to model the effect(s) of covariates on the LOS. As a secondary analysis, the association of covariates with the extended LOS (>9 days) was also investigated using logistic regression. Results: Our study showed that female sex, age, Medicaid insurance, and race were associated with a longer LOS. Most importantly, a diagnosis of depression was associated with a significantly longer LOS (1.05 times longer: 95% CI: 1.04-1.06) and was independently associated with 1.83 times higher odds (95% CI: 1.50-2.23) of belonging to the extended LOS group. Compared to 2007, significant reductions of both LOS and a longer LOS were noted throughout all later years from 2008 to 2010. Conclusions: Our study revealed that a diagnosis of depression and patient's characteristic such as age, female sex, Medicaid, nonwhite race resulted in a statistically significant increased LOS. These findings can be useful for planning and resource allocation for total knee replacement programs. Keywords: Length of stay, Total knee arthroplasty (TKA), Depression